2005
DOI: 10.1111/j.1600-0528.2005.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between parenting stress and the development of early childhood caries

Abstract: Our findings suggest the need to conduct longitudinal studies to give proper consideration to the temporal aspect of caries development and clarify the results obtained by on the relationship between parenting stress and oral health. Further study is also warranted to more clearly elucidate the association between social desirability (defensive responding) in parents and their children's ECC experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 13 publications
1
35
1
9
Order By: Relevance
“…Recent studies have searched for the reasons, emphasizing psychosocial factors. Parental stress has been reported as a potential risk factor for caries in preschool children 14,17,18 , and parents' and caregivers' cognitive characteristics have also been associated with caries in this group 19 . Other psychosocial factors, like alcohol abuse in the family and maternal psychiatric disorders have been associated with this condition 14,15,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have searched for the reasons, emphasizing psychosocial factors. Parental stress has been reported as a potential risk factor for caries in preschool children 14,17,18 , and parents' and caregivers' cognitive characteristics have also been associated with caries in this group 19 . Other psychosocial factors, like alcohol abuse in the family and maternal psychiatric disorders have been associated with this condition 14,15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Living conditions and psychosocial aspects of the family context can also contribute to the development of caries, including mental disorders 14,15,16,17,18 and cognitive factors 19 . Multivariate analyses and longitudinal studies on this topic are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown that the level of routines and flexibility of people's daily activities influences tooth brushing behaviour [Abegg et al, 2000], indicating the potential importance of the family functioning domains 'organization', 'structure' and 'routines' in child oral health. Studies using the Parenting Stress Index have demonstrated that the domain 'total parenting stress' was associated with higher levels of dental caries in children [Quiñonez et al, 2001;Tang et al, 2005;Menon et al, 2013]. However, the majority of the identified family functioning domains are emotional factors that focus on interpersonal interactions within the family, such as 'cohesion/engagement', 'involvement', 'communication', and also less common domains such as 'conflict' and 'affect'.…”
Section: Discussionmentioning
confidence: 99%
“…Typical co-morbidity of low-income individuals is the psychological distress, 54,92 which also may interest children 97 and exert a negative effect on ECC. [98][99][100] Indeed, individuals with co-morbidities frequently concentrate their attention on only one condition, not necessarily the most serious, and not necessarily ECC. 54,92,101,102 Fatalism is the view that we are powerless to do anything other than what we actually do 103 and is widespread amongst low-income communities and groups.…”
Section: Identification Of Appropriate Outcomesmentioning
confidence: 99%